Flipped Classroom Module on Shock for Medical Students - Jennifer A. Hoffmann (Association of American Medical Colleges, 2017)
Introduction This module teaches medical students about shock through a flipped classroom approach. By the conclusion of the module, students are able to differentiate the main types of shock, recognize clinical signs of shock, and formulate initial treatment plans. The flipped classroom approach means that students complete the lower levels of cognitive work (gaining knowledge and comprehension) outside of class, so that they can focus on the higher forms of cognitive work (application, analysis, synthesis, and evaluation) in class with the support of their peers and instructors. Methods Prior to class, students complete advance preparation by reading selected articles. In class, students work through case-based discussion questions in teams. Results This module has been successfully implemented, with survey data from students showing higher self-rated confidence in their ability to achieve specified objectives after completion of the module. According to survey data, students felt they learned more from the class than from a traditional lecture format, and the class promoted teamwork skills. Discussion This module provides a tool for pediatric faculty instructors to redesign a traditional lecture-based class on shock into an interactive, case-based session that uses the flipped classroom approach.